2021
DOI: 10.3389/fnagi.2021.695275
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Memory Complaints and Decision Making in Young and Older Adults: An Event-Related Potential Study

Abstract: Subjective memory complaints (SMCs) may affect decision-making processes. This study aimed to investigate the neuronal correlates of feedback processing during a decision-making task in young and older adults with and without SMCs. Event-related potentials and behavioral performance during the Iowa gambling task were recorded in a total of 136 participants (65 young adults, 71 older adults). The participants were divided into two groups according to their SMCs (with SMCs: n = 60, without SMCs: n = 76). Feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…In addition, a few longitudinal follow-up and prospective analyses were conducted. The descriptive studies corroborated the existence of a direct relationship between subjective cognitive complaints and the impairment of several executive processes, such as attention, working memory, initiative, cognitive flexibility, inhibition, planning, monitoring, verbal fluency, decision making and goal-directed behaviors [36,39,42,[45][46][47][48]. These functions were directly associated with selfreported complaints from participants but also their informants [34,41,43,44].…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…In addition, a few longitudinal follow-up and prospective analyses were conducted. The descriptive studies corroborated the existence of a direct relationship between subjective cognitive complaints and the impairment of several executive processes, such as attention, working memory, initiative, cognitive flexibility, inhibition, planning, monitoring, verbal fluency, decision making and goal-directed behaviors [36,39,42,[45][46][47][48]. These functions were directly associated with selfreported complaints from participants but also their informants [34,41,43,44].…”
Section: Resultssupporting
confidence: 63%
“…Among them, the most used tests assessed verbal and semantic fluency, cognitive processes such as working memory (digits—WAIS), attentional control (digits, symbol-substitution test and TMT A–B), initiation/perseveration (Korean rating scale K-DRS), BRIEF-A and inhibitory control (Stroop test). On the other hand, not all but some of the studies complemented the neuropsychological assessment with biological markers in the CSF or the use of neuroimaging [ 37 , 38 , 40 , 43 , 45 , 48 ]. Despite the high cost of neuroimaging studies and their limitations in terms of specificity and power resolution in the initial clinical analysis, which limits their applicability in the population with subjective cognitive complaints, the studies related executive performance to the presence of biomarkers in the CSF and to reductions detected by regional volumetric analyses.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that cut-off points and categorical distinctions are used in clinical procedures and may be helpful to neuropsychologists using this questionnaire. Partial results from the older subsample have been previously reported (Garrido-Chaves et al, 2021;Perez et al, 2021).…”
Section: Participantsmentioning
confidence: 83%
“…Some studies found no significant differences in P300 amplitude or latency between SCD patients and controls [ 17 , 47 , 48 ]. However, Smart et al [ 49 ] found a reduced P300 amplitude in SCD patients, suggesting a decline in attention capacity.…”
Section: Resultsmentioning
confidence: 99%